Competition and Stability: An Analysis of the Turkish Banking System - Omer Iskenderoglu; Serpil Tomak (International Journal of Economics and Financial Issues, 2013)
This paper examines the relationship between competition and stability in the Turkish banking sector using quarterly bank level data of 15 private commercial banks (domestic and foreigned-owned) between 2002-2012. There have been many theories stand out on the relationship between competition and stability of the banking sector so far. But theories of the competition-fragility view and competition-stability view are widely accepted theories in the literature. Dynamic panel data approach is employed to test the related tehories. However our findings indicate that the relationship between concentration and competition is not clear enough to emphasize a strict inference.